(untitled) (Bangladesh Journal of Plant Taxonomy, 2023)
During the floristic explorations conducted in 2022–2023 in different forest areas of the northeast region of Bangladesh, some specimens of the family Lauraceae were collected. Following critical examination, these specimens have been identified as belonging to the species Litsea kurzii, Litsea stocksii, and Litsea variabilis of the family Lauraceae. These species are new to the flora of Bangladesh. A detailed taxonomic description, including data on ecology, distribution, and use, a list of representative specimens examined, and photographs of each of these species have been provided. Bangladesh J. Plant Taxon. 30(1): 89–97, 2023 (June)